Variáveis aleatórias discretas. - OLIVEIRA, Gilberto Silva (Universidade Federal do Tocantins, 2023)
In this work we present the study of random and the measures of probability inherent in them. A component of this study is made up of random variables of discrete type. In these, the as- sociation X = xj, occurs under a certain measure of probability P defined by a probability sequence pj where j assume a finite set of values j = 1, 2, 3, · · · , n or an set of infinite va- lues j = 1, 2, 3, · · · . The object of our study are those discrete probabilistic models that and has contributed decisively to the development of the mathematical theory of Probabilities such as Bernoulli model, model Binomial, Geometric, Negative Binomial, Hypergeometric and Poisson, and which has been thoroughly studied by mathematicians such as Bernoulli, Pascal, Fermat, Laplace and others.